2006
DOI: 10.1002/adma.200502060
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fabrication of Poly(3,4‐ethylenedioxythiophene) Nanocapsules and Mesocellular Foams Using Surfactant‐Mediated Interfacial Polymerization

Abstract: Recently, there has been great interest in the fabrication and application of nanomaterials with diverse structures. Interfacial polymerization (IP) [1] has enabled the fabrication of specific architectures such as films, fibers, and membranes. [2] Recently, considerable effort has been devoted to the synthesis of conducting-polymer nanomaterials using IP. Most previous studies have focused on polypyrrole (PPy) or polyaniline (PANi) nanostructures. [3] In contrast, there is not much information available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 66 publications
3
48
1
Order By: Relevance
“…However, for BaTiO 3 @PEDOT composites, a faint oxidation peak can be observed at 0.25 V, and the reverse reduction wave is visible at -0.25 V. These peaks may be due to the redox transition of PEDOT between a semiconducting state and a conducting state. Similar peaks were observed by Jang et al in their electrochemical study of PEDOT nanoparticles [35].…”
Section: Electrochemical Property Of the Batio 3 @Pedot Compositessupporting
confidence: 79%
“…However, for BaTiO 3 @PEDOT composites, a faint oxidation peak can be observed at 0.25 V, and the reverse reduction wave is visible at -0.25 V. These peaks may be due to the redox transition of PEDOT between a semiconducting state and a conducting state. Similar peaks were observed by Jang et al in their electrochemical study of PEDOT nanoparticles [35].…”
Section: Electrochemical Property Of the Batio 3 @Pedot Compositessupporting
confidence: 79%
“…The second case has been realized by using a wide variety of soft templates (e.g., surfactants, polyelectrolytes, and liquid crystals) [216][217][218][219][220][221][222] and hard templates (e.g., colloidal nanoparticles and porous materials). 223,224 It is usually difficult to create nanoporous polymer structures under polymerization or casting conditions due to thermodynamic instability, in contrast with the case of porous silica families such as MCM-41 and SBA-15.…”
Section: Polymer Nanostructuresmentioning
confidence: 99%
“…A recent study demonstrated that the socalled "surfactant-mediated interfacial polymerization" was effective to selective fabrication of PEDOT nanostructures with nanometer-sized cavities. 219 At first stage, cationic ammonium surfactants with different alky chain lengths were used to form micelles in aqueous solution. The micelles were able to capture the redox initiator (CAN) due to electrostatic interactions between the cerium complex and the surfactant molecules, and the chemical polymerization of EDOT monomer proceeded at the micellar surface.…”
Section: Polymer Nanostructuresmentioning
confidence: 99%
“…Recently, PoPD hollow spheres decorated with Au and AgNs using monomer droplet method [10] have been reported. In this method, PoPD hollow spheres are synthesized in aqueous media, by means of the droplet template formed by the monomer itself without the aid of acidic reagent [11], surfactants [12] or hard templates [13]. These droplets (reactive template) formed by the monomer in aqueous solution are proposed to act as a template during the polymerization process [14].…”
Section: Introductionmentioning
confidence: 99%